2016
DOI: 10.1128/aac.00325-16
|View full text |Cite
|
Sign up to set email alerts
|

8-Hydroxyquinolines Are Boosting Agents of Copper-Related Toxicity in Mycobacterium tuberculosis

Abstract: c Copper (Cu) ions are likely the most important immunological metal-related toxin utilized in controlling bacterial infections. Impairment of bacterial Cu resistance reduces viability within the host. Thus, pharmacological enhancement of Cu-mediated antibacterial toxicity may lead to novel strategies in drug discovery and development. Screening for Cu toxicity-enhancing antibacterial molecules identified 8-hydroxyquinoline (8HQ) to be a potent Cu-dependent bactericidal inhibitor of Mycobacterium tuberculosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 66 publications
0
42
2
Order By: Relevance
“…To compare cell lines, all 26 analogs were tested for cytotoxicity against Vero cells; all active analogs were cytotoxic in this cell line as well (Table 4). These cytotoxicity data are in contrast to results from other groups, where cytotoxicity for 8-hydroxyquinoline (1) and related compounds was not noted (Ananthan et al, 2009;Darby & Nathan, 2010;Shah et al, 2016). The differences in these data may reflect the status of cells in the cytotoxicity assay, since, similar to our findings, Shen et al found HQ analogs to be cytotoxic via inhibition of DNA synthesis in HepG2 cells (Shen, Chen, & Roffler, 1999).…”
Section: Cytotoxicitycontrasting
confidence: 80%
See 2 more Smart Citations
“…To compare cell lines, all 26 analogs were tested for cytotoxicity against Vero cells; all active analogs were cytotoxic in this cell line as well (Table 4). These cytotoxicity data are in contrast to results from other groups, where cytotoxicity for 8-hydroxyquinoline (1) and related compounds was not noted (Ananthan et al, 2009;Darby & Nathan, 2010;Shah et al, 2016). The differences in these data may reflect the status of cells in the cytotoxicity assay, since, similar to our findings, Shen et al found HQ analogs to be cytotoxic via inhibition of DNA synthesis in HepG2 cells (Shen, Chen, & Roffler, 1999).…”
Section: Cytotoxicitycontrasting
confidence: 80%
“…Three analogs (14,15,18) showed no measurable cytotoxicity against HepG2 cells, but none of these were active against M. tuberculosis. These cytotoxicity data are in contrast to results from other groups, where cytotoxicity for 8-hydroxyquinoline (1) and related compounds was not noted (Ananthan et al, 2009;Darby & Nathan, 2010;Shah et al, 2016). To compare cell lines, all 26 analogs were tested for cytotoxicity against Vero cells; all active analogs were cytotoxic in this cell line as well (Table 4).…”
Section: Cytotoxicitycontrasting
confidence: 61%
See 1 more Smart Citation
“…Even more encouraging are antibiotics that can kill bacteria extensively, not only when they are replicating but also when they are not replicating and are phenotypically tolerant to other antibiotics. With respect to TB, this has been reported with 8-hydoxyquinolines ( Darby and Nathan, 2010 ; Shah et al, 2016 ) and nitazoxanide, an antibiotic approved for other indications ( de Carvalho et al, 2009 ). In vitro, the nitroimidazole PA-824 (pretomanid) kills both replicating and nonreplicating Mtb to comparable extents and at comparable concentrations ( Singh et al, 2008 ; Gold and Nathan, 2017 ).…”
Section: Is It Possible To Find New Antibiotics That Can Kill Bacterimentioning
confidence: 92%
“…Compound 30 , a 5-chloro, 7-bromo-substituted 8-hydroxyquinoline inhibitor of methionine aminopeptidase, killed M. tuberculosis that had been in stationary phase for two months (114). Some 8-hydroxyquinolines may mediate toxicity by chelating metals essential for mycobacterial survival, or by forming metal-quinoline complexes that engage target enzymes (211). …”
Section: Class II Persisters: a Majority Population Of Nonreplicatmentioning
confidence: 99%